ALTERNATIVE COMPLEMENTARY SERVICES OF SAPONIN TOWARDS REDUCTION OF FASTING BLOOD SUGAR LEVELS AND 2 HOURS POST PRANDIAL IN TYPE II DIABETES MELLITUS PATIENTS - Ni Nyoman Linawati; Suharyo Hadisaputro; Mardiyono Mardiyono (Bina Sehat Press. Departement Research and Community Engagement Bina Sehat PPNI Institute of Health Science, Indonesia, 2022)
Background - Diabetes mellitus (DM) is a metabolic disorder disease characterized by hyperglycemia. DM disease control aims to reduce mortality and morbidity, prevent complications and improve the quality of life of DM patients. DM treatment is carried out in a lifetime, requires large costs, causes mild to dangerous side effects, and requires a high level of medication adherence. Therefore, it is necessary to conduct an intervention that is cheap, easy to obtain and minimal risk. Objective - To prove that the administration of saponins has an effect on reducing fasting blood sugar levels and 2 hours post prandial in patients with type 2 DM. Methods - From 37,195 journals accessed full text, 18 journals were obtained from the screening results that met the inclusion criteria for a systematic literature review with the design used in this study used a randomized control trial design, quasi-experimental, and pre-clinical trial published in the 2015-2020 range. The subject of this study is related to saponins, fasting blood glucose, 2 hours pp in patients with type 2 diabetes. Results - Giving saponins to aloe vera plants with doses in the range of 300-500 mg/day is more effective in reducing fasting blood sugar levels with p value= 0.000 and effect size 1.42 (very strong) compared to other plants. Meanwhile, the saponin content in cherry plants with a dose of 15 grams was more effective in reducing fasting blood sugar levels 2 hours post prandial in patients with type 2 diabetes mellitus compared to other plants with p value= 0.000 and effect size 2.85 (very strong). Conclusion - Based on the results of the analysis of the research subjects, that the saponin intervention was very effective in reducing fasting blood sugar levels and 2 hours of PP.